Police Discretion In Narcotics Cases Committed By Minors In The Jurisdiction Of Bali Regional Police - Moch Arie Surahman; Nurianto RS; I Nyoman Suandika (PT Publikasiku Academic Solution, 2025)
The application of police discretion in the process of diversion of narcotics cases carried out by minors in the jurisdiction of the Bali Police. Using empirical juridical methodology, this study analyzes the regulation and implementation of police discretion in the context of positive law in Indonesia, especially related to Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and Law Number 35 of 2009 concerning Narcotics. The results of the study show that police discretion plays an important role in handling narcotics cases involving children, with the aim of avoiding children from the formal judicial process which can negatively impact their mental and social development. Diversion is expected to be a better alternative solution, which takes into account not only the interests of the law but also the welfare of the child. However, this study also identifies various obstacles in the application of discretion, including lack of understanding among law enforcement, challenges in implementing diversion procedures, and social stigma against children of criminal offenders. This study recommends the need to increase the capacity of law enforcement and socialize the importance of the restorative justice approach in handling narcotics cases involving children. Thus, this study emphasizes the importance of law enforcement oriented towards child protection and rehabilitation, as an effort to prevent children from falling further into criminal behavior.